2009
DOI: 10.1016/j.pupt.2008.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of higher than standard doses of salbutamol and ipratropium on tiotropium-induced bronchodilation in patients with stable COPD

Abstract: Please cite this article as: Cazzola M, Santus P, D'Adda A, Pizzolato S, Di Marco F, Centanni S. Acute effects of higher than standard doses of salbutamol and ipratropium on tiotropiuminduced bronchodilation in patients with stable COPD, Pulmonary Pharmacology & Therapeutics (2008), doi: 10.1016/j.pupt.2008 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…6 Previous studies have demonstrated that SABA is more effective for resting pulmonary function parameters than SAMA in stable COPD patients with a regular treatment with LAMA. 15,16 In this study, the additive efficacy of SABA on airflow limitation, dynamic hyperinflation and exercise tolerance was superior to that of SAMA in stable COPD patients treated with LAMA. These findings suggest that SABA is better to use for relief of dyspnea as-needed in stable COPD patients regardless of regular treatment with LAMA.…”
Section: Discussionmentioning
confidence: 66%
“…6 Previous studies have demonstrated that SABA is more effective for resting pulmonary function parameters than SAMA in stable COPD patients with a regular treatment with LAMA. 15,16 In this study, the additive efficacy of SABA on airflow limitation, dynamic hyperinflation and exercise tolerance was superior to that of SAMA in stable COPD patients treated with LAMA. These findings suggest that SABA is better to use for relief of dyspnea as-needed in stable COPD patients regardless of regular treatment with LAMA.…”
Section: Discussionmentioning
confidence: 66%
“…33 Using higher doses, there is no substantial difference between using a short-acting beta-agonist or a short-acting muscarinic agonist. It has also been demonstrated that there is an effective improvement in FEV 1 on adding a high dose of salbutamol (600 μg) or a high dose of ipratropium bromide (120 μg) to regular tiotropium 34. A limitation of this study is the fact that we only studied patients with more severe GOLD Stage III COPD who are known to have more volume response.…”
Section: Discussionmentioning
confidence: 97%
“…The use of an SABA + SAMA combination may be more effective than the use of each of these drugs separately and may help to reduce the diurnal variability in FEV 1 40. It is possible to use the short-acting bronchodilators in addition to the long-acting drugs since their effectiveness in this situation has been supported by several studies 41,42…”
Section: Implementing the New Copd Algorithm For Copd Treatment In Rementioning
confidence: 99%